Perspectiva docente sobre a aprendizagem e desenvolvimento das crianças da educação infantil em Tocantinópolis no período pandêmico - Silva, Indiana Pereira Paulo Da (Universidade Federal do Tocantins, 2023)
This work has as its theme the teaching perspective on the learning and development of children in kindergarten in Tocantinópolis during the pandemic period. Through this study, the objective was to analyze, from the perspective of the pandemic, the impact on the learning and development process of children in kindergarten in Tocantinópolis, from the perspective of teachers, and how students and teachers adapted to the changes generated by isolation. Social. Coupled with this objective, we also discuss the context of the pandemic and the relationship with the research theme, about what a pandemic is, its characterization and impacts, making several notes about the World Health Organization WHO and about the trajectory of the Unified Health System. SUS Health. In the second chapter, we address the legal parameters for learning and development in early childhood education, according to the National Curriculum Guidelines for Early Childhood Education (DCNEI), National Common Curricular Base (BNCC) and the Tocantins Curricular Document (DCT). Where, to support our research, we will deal with what the legal documents say, emphasizing learning rights and fields of experience in early childhood education. In the third chapter, we present the research carried out with teachers in kindergartens and preschools in Tocantinópolis. We analyzed the impacts on the learning and development process in children in early childhood education in Tocantinópolis and whether learning occurred within the learning rights and fields of experience in early childhood education that DCNEI, BNCC and DCT present. As a method for data collection, we used a questionnaire prepared in Google Form sent to teachers. We opted for qualitative data analysis. The participants' responses provided a rich debate on the subject, the implications of teaching in the context of the Covid-19 pandemic were verified. It evidenced the lack of continued training of teachers with technological resources. Despite trying to reinvent themselves. It made us reflect on how to work with children to interact in the middle of the pandemic through experiences with more intentionality. Finally, it is evident that investing in the continuing education of teachers is essential, especially in mediating practices of technology, so that, in the midst of the crisis, access to education is something concrete.